The announcement of Dar al-Harb in cyber media in context of the theological policy of jihad: reading the cyber-jihad and ISIS based on the pharmakon characteristic of the cyber media - Erdem, Burcu Kaya; Bilge, Remzi (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
‘Pharmakon’ is a dualist word which means remedy or poison, or neither remedy nor poison, and it was used by Jacques Derrida in the Pharmacy of Plato (La Pharmacie de Platon - 1972) where he made a structural analysis of Plato's dialog with Phaedrus. Some think that it is a remedy; it is beneficial, and it produces and mends. Others think that it is a poison, because it makes you forget, makes you become distant to the truth, and isolates you from reality. This is similar to the character of cyber media, which is considered as both a remedy and a poison, indicating a widely-accepted dilemma between its purposes and conditions when it was first created and the form of usage today. This is related to the fact that cyber media is being discussed once again after the announcement of cyber-jihad by ISIS (Islamic State of Iraq and Syria), since some believe that radical Islam is a remedy, and others believe that it makes you become distant to the truth and turns a defensive tool into an antagonistic weapon.